Sporozoite neutralizing antibodies elicited in mice and rhesus macaques immunized with a Plasmodium falciparum repeat peptide conjugated to meningococcal outer membrane protein complex - Przysiecki, Craig; Lucas, Bob; Mitchell, Robert; Wen, Zhiyun; Carapau, Daniel; Wang, Xin-Min; Nahas, Debbie; Wu, Chengwei; Hepler, Robert; Ottinger, Elizabeth; ter Meulen, Jan; Kaslow, David; et al. (Frontiers in Cellular and Infection Microbiology, 2012)
Antibodies that neutralize infectivity of malaria sporozoites target the central repeat region of the circumsporozoite (CS) protein, which in Plasmodium falciparum is comprised primarily of 30–40 tandem NANP tetramer repeats. We evaluated immunogenicity of an alum-adsorbed (NANP)6 peptide conjugated to an outer membrane protein complex (OMPC) derived from Neisseria meningitidis, a carrier protein used in a licensed Haemophilus influenzae pediatric vaccine. Mice immunized with (NANP)6-OMPC adsorbed to Merck's alum adjuvant (MAA), with or without Iscomatrix® as co-adjuvant, developed high levels of anti-repeat peptide antibody that inhibited in vitro invasion of human hepatoma cells by transgenic P. berghei sporozoites that express P. falciparum CS repeats (PfPb). Inhibition of sporozoite invasion in vitro correlated with in vivo resistance to challenge by the bites of PfPb-infected mosquitoes. Challenged mice had >90% reduction of hepatic stage parasites as measured by real-time PCR, and either sterile immunity, i.e., no detectable blood stage parasites, or delayed prepatent periods which indicate neutralization of a majority, but not all, sporozoites. Rhesus macaques immunized with two doses of (NANP)6-OMPC/MAA formulated with Iscomatrix® developed anti-repeat antibodies that persisted for ~2 years. A third dose of (NANP)6-OMPC/MAA+ Iscomatrix® at that time elicited strong anamnestic antibody responses. Rhesus macaque immune sera obtained post second and third dose of vaccine displayed high levels of sporozoite neutralizing activity in vitro that correlated with presence of high anti-repeat antibody titers. These preclinical studies in mice of different MHC haplotypes and a non-human primate support use of CS peptide-OMPC conjugates as a highly immunogenic platform to evaluate CS protective epitopes. Potential pre-erythrocytic vaccines can be combined with sexual blood stage vaccines as a multi-antigen malaria vaccine to block invasion and transmission of Plasmodium parasites.